1989
DOI: 10.1002/jsfa.2740490412
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of air‐classified yellow pea (Pisum sativum)fractions

Abstract: The objective of the present investigation was the characterisation of yellow pea (Pisum sativum L) fractions obtained on a commercial scale by air classification of the milled peas. Some analytical aspects of the process were investigated including particle size distribution of fractions and their functional properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Han and Kahn (1990) studied navy beans, pinto beans, and chick-peas and found that starch-rich fractions (coarse particle size) had the highest water-holding capacity, nitrogen solubility, and cold paste viscosity, whereas protein-rich fractions (fine particle size) were superior in emulsification and foamability. Horvath et al (1989) found similar results with air-classified yellow pea fractions, where fine fractions were high in protein and exhibited greater oil absorption capacity, emulsifying activity, and stability. They also determined that coarse fractions (>16 µm) were characterized by high water absorption capacities.…”
Section: Functional Propertiessupporting
confidence: 67%
“…Han and Kahn (1990) studied navy beans, pinto beans, and chick-peas and found that starch-rich fractions (coarse particle size) had the highest water-holding capacity, nitrogen solubility, and cold paste viscosity, whereas protein-rich fractions (fine particle size) were superior in emulsification and foamability. Horvath et al (1989) found similar results with air-classified yellow pea fractions, where fine fractions were high in protein and exhibited greater oil absorption capacity, emulsifying activity, and stability. They also determined that coarse fractions (>16 µm) were characterized by high water absorption capacities.…”
Section: Functional Propertiessupporting
confidence: 67%
“…There are also numerous studies about the use of micronization and air classification in flours from peas (Horv ath et al, 1989), beans Khan, 1990a, 1990b;Patel et al, 1980) and other legumes (Sosulski and Youngs, 1979;Tyler et al, 1981). Nevertheless, the majority of these studies are also based on the nutritional properties of these fractions.…”
Section: Fine Grinding and Air Classificationmentioning
confidence: 95%
“…Apart from the differences in composition, the fractions also differ in their nutritional properties, such as water-holding capacity, emulsifier properties, oil-holding capacity and pasting properties (Han & Khan, 1990;Horvath, Ormai-Cserhalmi, & Czukor, 1989;Sosulski, Hoover, Tyler, & Murray, 1985). These differences mean that the two fractions have different applications.…”
Section: Introductionmentioning
confidence: 95%